Immunohistochemical study of PDGF, IGF of radiated tooth rat embryo - Shanaz M Gaphor; Mustafa J Abdullah (College of Dentistry/ University of Baghdad, 2014)
Background: Oral health is important to the quality of life of all individuals. Oral lesions can cause discomfort or pain that interferes with mastication, swallowing, and speech. Oral disease is a health problem that is not only a matter of oral hygiene and local condition, but can also be a precursor to other dangerous and potentially life threatening illnesses. The present study was designed to analyze the main clinicopathological aspects of most common oral lesions in patients who visit the Oral Diagnosis Clinic of the College of Dentistry, University of Sulaimani, Kurdistan region, Iraq. Patients and methods: This prospective study was performed on 3144 patients from July 2009-July 2010. In this study a total of 3144 patients were examined. Of these 1507 (47.93%) were males and 1637 (52.06%) females. The patients' age ranged between 10 to 79 years. An interview was conducted to collect information using a structured questionnaire which was completed by each patient. The lesions that could not be diagnosed by clinical examinations alone were analyzed histopathologically. Results: Among 3144 patients, only 799 patients (25.41%) had oral lesions. Females constituted 49.81% (n=398) and males 50.18 (n=401). The age range of the patients was between 10-79 years with a mean age of 33.75 years. Anatomic changes and developmental anomalies were considered as linea alba (16.68%), Fordyce's granules (12.37%), torus mandibularis (0.66%), torus palatinus (0.55%). Common oral lesions after those considered being anatomic changes and developmental anomalies were fissure tongue (18.23%), cheek biting (12.15%), hairy tongue (6.51%), and recurrent aphthous stomatitis (5.85%) , ankyloglossia (3.75%) , lingual varicosities (2.87%) , frictional (traumatic) keratosis (2.87%) , denture stomatitis (2.54%), recurrent herpes simplex virus infection (2.43%), traumatic ulcer (2.43%), geographic tongue (1.98%), fibroepithelial hyperplasia (1.32%), denture induced fibrous hyperplasia (1.21%) , angular cheilitis (0.99%) , oral lichen planus (0.88%) , median rhomboid glossitis (0.88%) , peripheral giant cell granuloma (0.22%) , and gingival hyperplasia (0.33%) . Conclusion: Routine examinations of oral cavities are valuable in identifying several oral lesions and this will help to establish early diagnosis and treatment and better prognosis particularly early precancerous and other oral lesions.